"Neither Precisely National nor Precisely Federal": Governmental and Administrative Authority in Tocqueville's Democracy in America. Issue 4 (7th August 2018) - Bambrick, Christina
Abstract: Tocqueville's insights on local politics in Democracy in America have led some scholars to ask where he fits into longstanding debates about the balance of power between the national government and state governments in American constitutionalism. Although Tocqueville's observations speak to these questions, he also transcends them by developing the concepts of governmental and administrative (de)centralization . In differentiating governmental and administrative capacities, Tocqueville offers language by which to understand and evaluate the federal system in terms of the nature of the authority each level of government exercises, rather than simply by the objects of national, state, and municipal powers. The purpose of this article is to clarify Tocqueville's understanding of governmental and administrative (de)centralization and thereby contribute to a better understanding of political authority in the American federal system.